Comunidades negras rurales de Antioquia : discursos de ancestralidad, titulación colectiva y procesos de “aprendizaje” del Estado (2015)
ABSTRACT: The following article analyzes how different actors involved in the process of collective land titling of afro-Colombian territories in Antioquia construct discourses about the ancestral occupation of the land. The article describes the variety of migratory processes that have configured black rural communities in Antioquia over the past four decades, as registered in land titling records and as observed in two case studies. Contrasting with this variety of experiences, the process of land titling has consolidated a homogenizing official discourse that professes continuity between the back rural territories of today and those occupied by cimarrones in the eighteenth century. The article argues that processes of reception, learning, re-signification and appropriation of discourses of ancestrality occur within communities as well as amongst State functionaries.